Assessing the Efficacy and Safety of Bimodal Neuromodulation for the Management of Symptomatic Tinnitus - Subramaniam, Thavakumar (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2021)
Tinnitus is defined as the perception of sound in the absence of an external auditory stimulus. It is a common symptom, affecting 5 30% of the general population, however only 1 3% of patients report the symptom to be intrusive or bothersome. The exact pathophysiology of tinnitus is not clearly understood, however it is hypothesized that a reduction in peripheral auditory input may result in discoordinated activity within the auditory neural pathways. Hence, tinnitus is commonly associated with sensorineural hearing loss and the prevalence of tinnitus has been observed to increase after 70 years of age due to presbycusis. Tinnitus is also frequently reported by patients with hearing loss secondary to chronic loud sound exposure, such as in the case with military personal. Tinnitus is the most common disability affecting American military veterans, with an estimated 1.2 billion dollars spent in compensation annually. There is a growing volume of evidence to support the involvement of non-auditory central structures in tinnitus activity such as the limbic system and dorsal cochlear nucleus. Hyperactivity within the limbic system may be linked to the strong psycho-emotional response often associated with tinnitus. The dorsal cochlear nucleus is a key site for neural convergence, receiving neural input from the auditory pathway, limbic system, cranial nerves and cervical spine nerve root ganglia. There is a growing volume of evidence to suggest that the dorsal cochlear nucleus is a key site involved in generating and sustaining tinnitus activity. A gold standard treatment option for tinnitus remains illusive. To date, no drug therapy has been shown to be completely safe or clinically efficient. There is evidence to support the efficacy of cognitive behavioural therapy as a treatment option for tinnitus symptom control. However this modality aims to improve the patient s response to tinnitus, rather than eliminating or reducing the severity of the symptom. Neuromodulation has emerged as a potential effective treatment option for tinnitus. In general, this novel therapeutic modality aims to alter neural activity by delivering a targeted stimulus. There is evidence from both animal and human studies that show modulation of tinnitus activity can be achieved, by stimulating the auditory neural pathways, either directly or via an interconnected neural network. Multiple neuromodulation stimulation techniques have been designed and investigated, however no modality has been shown to be superior in achieving optimal clinical gains for tinnitus. However, there is emerging evidence to support the use of bimodal stimulation techniques to achieve greater therapeutic gains during tinnitus treatment. The benefits of bimodal stimulation were initially observed in animal studies. The pairing of auditory and electrical stimulation had the therapeutic advantage of suppressing neural hyperactivity in animals exhibiting tinnitus behaviour. Neuromod Devices Limited (Neuromod Ltd) has developed a CE marked medical device called MutebuttonTM that enables bimodal neuromodulation for the treatment of tinnitus, combining auditory and electrical stimulation. Auditory stimulation in the form of frequency-adjusted tones, are used to stimulate auditory pathways involved in tinnitus. Electrical impulses stimulate the trigeminal nerve (via the lingual nerve) through an anterior tongue surface probe. Relevant to this design is evidence supporting the use of anterior tongue stimulation to drive greater auditory neuroplastic changes. The efficacy of the MutebuttonTM device was initially assessed in the Tinnitus Alleviation Via Sensory Stimulation (TAVSS) pilot study. This was a single arm study in which the recruited participants, (n = 54) underwent a 10-week treatment period. The findings from this study were encouraging with treatment compliant participants reporting statistically significant improvements in Tinnitus Handicap Index scores (mean improvements of 11.7 points, p<0.001). The TAVSS study also established the feasibility of the MutebuttonTM device as a potential treatment option for symptomatic tinnitus. The aim of this project was to build on the promising data observed in the TAVSS study. We designed a randomized double-blinded trial to assess the effects of three different bimodal stimulation settings on tinnitus severity. Based on both animal and human studies, variations in inter-stimulation settings (intensity and timing) have been shown to drive greater neuroplastic change that may be beneficial in reducing tinnitus activity. The trial was conducted at two sites, Wellcome Trust-HRB Clinical Research Facility, St James s Hospital, Dublin, Ireland and Tinnituszentrum Regensburg, University of Regensburg, Germany. The participants underwent a 12-week treatment period and were assessed at five clinical visits over a 12-month period. Treatment outcome measures were recorded at each visit using validated tinnitus research questionnaires. A secondary aim of this trial was to assess the safety and feasibility of the MutebuttonTM device. Trained technicians at the clinical research facilities carried out device safety checks and relevant clinical examinations of the study participants during each assessment. All adverse events reported by participants were classified and logged for data analysis. The outcomes reported in this study support the use of bimodal neuromodulation as a treatment option for symptomatic tinnitus. The variations in stimulations settings investigated during the trial have also shown to be beneficial in driving long-term therapeutic gains. These findings provide a strong basis upon which further research can undertaken.
APPROVED
Keywords: Tinnitus; Neuromodulation